The evolution of the coding exome of the Arabidopsis species - the influences of DNA methylation, relative exon position, and exon length - Chen, Feng-Chi (BioMed Central, 2014)
BACKGROUND: The evolution of the coding exome is a major driving force of functional divergence both between species and between protein isoforms. Exons at different positions in the transcript or in different transcript isoforms may (1) mutate at different rates due to variations in DNA methylation level; and (2) serve distinct biological roles, and thus be differentially targeted by natural selection. Furthermore, intrinsic exonic features, such as exon length, may also affect the evolution of individual exons. Importantly, the evolutionary effects of these intrinsic/extrinsic features may differ significantly between animals and plants. Such inter-lineage differences, however, have not been systematically examined. RESULTS: Here we examine how DNA methylation at CpG dinucleotides (CpG methylation), in the context of intrinsic exonic features (exon length and relative exon position in the transcript), influences the evolution of coding exons of Arabidopsis thaliana. We observed fairly different evolutionary patterns in A. thaliana as compared with those reported for animals. Firstly, the mutagenic effect of CpG methylation is the strongest for internal exons and the weakest for first exons despite the stringent selective constraints on the former group. Secondly, the mutagenic effect of CpG methylation increases significantly with length in first exons but not in the other two exon groups. Thirdly, CpG methylation level is correlated with evolutionary rates (d(S), d(N), and the d(N)/d(S) ratio) with markedly different patterns among the three exon groups. The correlations are generally positive, negative, and mixed for first, last, and internal exons, respectively. Fourthly, exon length is a CpG methylation-independent indicator of evolutionary rates, particularly for d(N) and the d(N)/d(S) ratio in last and internal exons. Finally, the evolutionary patterns of coding exons with regard to CpG methylation differ significantly between Arabidopsis species and mammals. CONCLUSIONS: Our results suggest that intrinsic features, including relative exonic position in the transcript and exon length, play an important role in the evolution of A. thaliana coding exons. Furthermore, CpG methylation is correlated with exonic evolutionary rates differentially between A. thaliana and animals, and may have served different biological roles in the two lineages.